2022
DOI: 10.1111/bcp.15558
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative glomerulonephritis after intravitreal vascular growth factor inhibitor injections: A case report and review of the literature

Abstract: Systemic administration of agents that inhibit vascular endothelial growth factor (VEGF) and therefore vascular proliferation is often used to treat various cancers. However, these agents are associated with a number of side effects, including proteinuria and renal injury. Intravitreal injection of anti‐VEGF agents has become the cornerstone of macular disease treatment. Since these agents cross the blood‐retina barrier and enter the circulation, systemic side effects have been reported. We report the novel ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
2
0
2
Order By: Relevance
“…(2006) encontraram em seus resultados que a perda da visão foi prevenida e a acuidade visual média de pacientes teve melhora com baixa taxa de eventos adversos e Bandello et al (2019) encontraram em um estudo sobre a segurança terapêutica do Ranibizumabe que houve poucos eventos adversos no uso desse medicamento, demonstrando sua segurança e tolerabilidade. Porém em um relato de caso Gan, et. al.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(2006) encontraram em seus resultados que a perda da visão foi prevenida e a acuidade visual média de pacientes teve melhora com baixa taxa de eventos adversos e Bandello et al (2019) encontraram em um estudo sobre a segurança terapêutica do Ranibizumabe que houve poucos eventos adversos no uso desse medicamento, demonstrando sua segurança e tolerabilidade. Porém em um relato de caso Gan, et. al.…”
Section: Discussionunclassified
“…al. (2022) relataram que um paciente de 57 anos em tratamento com Ranibizumabe para oclusão da veia central da retina apresentou glomerulonefrite após duas semanas da injenção do anti-VEGF (Gan et al, 2022).…”
Section: Discussionunclassified
“…Patients with extremely high or low eGFR have greater persistent eGFR decline during the long-term intravitreal administration of anti-VEGF treatment for two years in the patients with diabetic macular edema [ 29 ]. Gan et al reported that a patient with macular edema secondary to central retinal vein occlusion has membranoproliferative glomerulonephritis after intravitreal vascular growth factor inhibitor injections [ 30 ]. However, there is no clinically significant change in the serum markers of renal function during the short-term intravitreal treatment of anti-VEGF drugs for 1 month in the patients with neovascular age-related macular degeneration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uys et al reported that continuous bevacizumab use led to renal thrombotic microangiopathy (TMA) [ 38 ]. In addition, several cases of renal dysfunction and proteinuria have been reported after exposure to bevacizumab [ 26 , 27 , 28 , 30 , 32 ]. A previous study suggested that TMA was associated with a risk of CKD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%